ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DAN PENENTUAN HARGA JUAL ATAS PRODUK (Studi Kasus Pada PT Dasa Windu Agung) - Wardoyo, Dwi Urip (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
This study aims to determine the determination of the cost of production for products produced by PT. DWA. The Company is engaged in the manufacturing industry specialized in automotive components. Its activity is carried out through a series of production processes, so that expenses spent in the production will be calculated into the cost of the production sold. The population in this study were all manufacturing companies in Jakarta. Convenience sampling method selected one of the companies that get the confidence to assemble three national car project in Indonesia, namely Timor, Bakrie and Maleo. Test analysis used in this study is to test the calculation of full costing with job order costing. This study shows that (a) determination of the cost elements associated with the cost of production and (b) determining the cost of production on a product-based job costing with full costing approach. Keywords: cost of production, full costing